Evaluation of Serum D-dimer Levels and the Disease Severity in Patients of Chronic Urticaria - Leelavathy Budamakuntla; Sachin Somashekar; Heera Ramesh; Tapasya S Kini; S Nandish Kumar (Clinical Dermatology Review)
Background: Urticaria is a common disorder. Besides autoimmunity, the coagulation pathway is also involved in the pathogenesis of chronic urticaria (CU). Previous studies showed that plasma D-dimer levels paralleled the severity of the disease. Objective: This study aimed to find the relationship between plasma D-dimer levels and the disease severity in patients with CU. Materials and Methods: The study population comprised 59 adult patients with CU recruited from the dermatology outpatient department in a tertiary care hospital. The patients enrolled in the study (by random sampling) were subjected to blood sampling for estimation of D-dimer levels after a thorough history and examination. Assessment of disease severity was estimated according to the Urticaria Activity Score 7, and the patients were classified into mild, moderate, and severe urticaria. All patients also underwent autologous serum skin test. Results: Out of the 59 patients, the D-dimer levels were increased in 59% (n = 35) of the patients and normal in 41% (n = 24) of patients. About 30.5% (n = 18) of patients had mild urticaria, 54.23% (n = 32) of the patients had moderate urticaria, and 15.25% (n = 9) of patients had severe urticaria. About 33.33% of the patients with mild urticaria had raised D-dimer levels, 71.87% of the patients with moderate urticaria had raised D-dimer levels, and 66.7% of the patients with severe urticaria had raised D-dimer levels. This study demonstrated a positive correlation between plasma D-dimer levels and severity of urticaria. Conclusion: Patients with CU show elevated D-dimer plasma levels. There was a positive correlation between plasma D-dimer levels and the severity of CU. Investigation for plasma D-dimer level may be an alternative way to evaluate disease severity in patients with chronic idiopathic urticaria.